Female athlete triad screening in national collegiate athletic association division I athletes: Is the preparticipation evaluation form effective? - Mencias, T.; Noon, M.; Hoch, A. Z. (Clinical Journal of Sport Medicine, 2012)
Objective: To evaluate the screening practices and preparticipation evaluation (PPE) forms used to identify college athletes at risk for the female athlete triad (triad).